Scientific communications of the 1920s: Development factors - Yu.B. Balashova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
The paper discusses the external and internal environment of science development in the 1920s. In this period, science, on the one hand, maintained continuity with respect to the pre-revolutionary paradigm and, on the other hand, it developed according to the avant-garde scenario. Science constituted a characteristic topic of the era. The channels of science mediatization included various institutional and non-institutional associations, press, and fiction literature. Thomas Kuhn, the famous science historian, identified several signs of the scientific revolutions. First of all, in scientific revolutions, the analogy with biological evolution is broken. Then, the conceptual discrepancy between different disciplines increases, and specialization grows. From the indicated principles, the scientific revolution in Russia – as well as in developed societies as a whole – happened at the turn of the 19th and 20th centuries. That is, social revolution does not automatically lead to irreversible upheavals in other areas. On the contrary, in the long run, the successes of many branches of the Soviet science (not only cosmonautics, but also at a certain stage of one of the most authoritative in the world, Soviet philological schools) were provided both by state support and by the specific action of the mechanisms of scientific continuity. The revolutionary reorganization of Russian society, disastrous for the country as a whole, was, nevertheless, accompanied by the original development of science communication.